Defining Stereotype Threat and Why It Matters - Brooks, Jaysson T. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Stereotype threat was coined by Dr. Claude Steele as a “socially premised psychological threat that arises when one is in a situation or doing something for which a negative stereotype about one’s group applies.” According to stereotype threat, members of a marginalized group acknowledge that a negative stereotype exists in reference to their group, and they demonstrate apprehension about confirming the negative stereotype while engaging in activities where their performance will be measured. Anyone can experience stereotype threat; however, in the field of orthopaedic surgery, stereotype threat is most likely experienced by racial and/or gender minorities. This article reviews salient literature related to stereotype threat and describes how to provide feedback to people who are experiencing stereotype threat.